Token based HVAC scheduling for a large building - Liew, Ke Chuan (2017)
In the recent years, the HVAC’s energy consumptions have accounted for a big chunk of the societal energy consumption as supported from the research showing that the 50% of the total energy consumption belongs to the HVAC system in the residential and commercial building. Considering the long-term problem of HVAC system, many researchers have looked into ways to reduce the heavy consumption caused by the HVAC system like using the token based approach, controlling strategies and many more. Hence, energy savings and efficiency are still the top priority in the long-term run. The purpose of this project is to develop an optimal controlling strategy in reducing the energy consumption by the HVAC system with the helps of MLE+. But firstly, a detailed model building with the HVAC system has to be built and then followed by the inputting of parameters into the model building using the help of software like Google SketchUp Make, OpenStudio and EnergyPlus. After which, the building model will service as a virtual test bed for the development of the controlling strategy. Furthermore, by studying the simulated results from EnergyPlus, it can also reduce the amount of energy consumption by the HVAC system by estimating the input parameters.